CO₂ fertilization of terrestrial photosynthesis inferred from site to global scales - Chen, Chi; Riley, William J.; Prentice, I. Colin; Keenan, Trevor F. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Global photosynthesis is increasing with elevated atmospheric CO₂ concentrations, a response known as the CO₂ fertilization effect (CFE), but the key processes of CFE are not constrained and therefore remain uncertain. Here, we quantify CFE by combining observations from a globally distributed network of eddy covariance measurements with an analytical framework based on three well-established photosynthetic optimization theories. We report a strong enhancement of photosynthesis across the observational network (9.1 gC m−2 year−2) and show that the CFE is responsible for 44% of the gross primary production (GPP) enhancement since the 2000s, with additional contributions primarily from warming (28%). Soil moisture and specific humidity are the two largest contributors to GPP interannual variation through their influences on plant hydraulics. Applying our framework to satellite observations and meteorological reanalysis data, we diagnose a global CO₂- induced GPP trend of 4.4 gC m−2 year−2, which is at least one-third stronger than the median trends of 13 dynamic global vegetation models and eight satellite-derived GPP products, mainly because of their differences in the magnitude of CFE in evergreen broadleaf forests. These results highlight the critical role that CFE has played in the global carbon cycle in recent decades.